SUBSTRATES, SEEDLING AGE AND ENVIRONMENT IN THE INITIAL GROWTH OF Cariniana pyriformis Miers - Prato, Andrés Iván; Sanchez, Shallon Natalia; Zuluaga, Jhon Jairo; Dutra de Souza, Paulo Vitor (Floresta, 2020)
T The massive production of high-quality seedlings can improve the conservation and commercial reforestation plans of the Colombian mahogany (Cariniana pyriformis Miers), a native forest species of Colombia. To contribute to this objective, two environments were evaluated. The first was an arched protected environment of structure covered with anti-thermal low-density polyethylene film to offer 50% shade and photoselective to U.V radiation, while the second was an agricultural nursery covered with black monofilament screen and mesh to offer 65% shading. Each environment adopted an experimental design of complete random blocks into a split-plot scheme. The main plot comprised five substrates that contained different volumetric proportions of river sand (SA), pine bark (PB), coconut fiber (CF), commercial compost obtained from composting poultry manure, cane dust and sawdust powder (CC), and subsoil from the study region (SS). The subplot was two seedling ages: 77 and 95 days after sowing. The values for the Dickson quality index, leaf area, dry mass of the aerial part and the root system, for both ages, was higher inside the protected environment. The agricultural nursery did not evidence substrates effect. For both environments and ages, optimal morphological attributes were not reached in the seedlings to be established in the field. The substrate based on 20% SA + 20% CC and 60% SS is the best as it increases seedling vigor, followed by the 20% PB + 20% CC + 60% SS composition.